Selectivity of herbicides in native forest species of cerrado (Bioscience Journal, 2018)
A aggravating problems in forest management is weed interference, which is a factor that modifies adaptation and reduces plant growth. The use of herbicides is an indispensable practice to mitigate these effects in reforestation areas. This study aimed to evaluate the selectivity of glyphosate and imazapyr in native plants of the Brazilian Cerrado, such as: Schinus terebinthifolia (Anacardiaceae), Peltophorum dubium (Fabaceae) and Handroanthus albus (Bignoniaceae). The trial was carried out in a greenhouse at Unit of Aquidauana/UEMS. Experimental design was completely randomized, with seven treatments and five replications. Selectivity of the herbicides in the seedlings of these species was evaluated at 7, 14, 21, 28 and 60 days after application (DAA) of the herbicides, by means of a percentage scale of notes, where 0% corresponds to no injury and 100% corresponds to plant death. At the same time, for the weed control evaluation, visual analysis was also performed at 7, 14, 21, 28 and 60 DAA of the herbicides, where 100% was considered plant death and 0% no injury to weed. Imazapyr herbicide, when applied in the initial post-emergence in its lower level, it is selective to the tree species, but in the other concentrations it can affect differently the survival of them. Glyphosate herbicide was the least selective to the tree species in its different concentrations, causing phytotoxic effects with changes in the seedlings morphology. The results of this study could help in the integrated management of weeds and contribute to the efficient herbicide use in planting forest species in the Cerrado.